PENGEMBANGAN BAHAN AJAR BARISAN DAN DERET MATEMATIKA BERBASIS MULTIMEDIA INTERAKTIF - Endro Setiawan; Swaditya Rizki (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
The objective of this development research was to produce the learning materials of sequence and series based on interactive multimedia that were valid and practical to use for the student. This research type was Research and Development (R&D). The model used in this research was Plomp model consisting of three phases, namely preliminary research, prototype, and assessment. The instrument used questionnaire consisting of two types of questionnaires, the first expert validation questionnaire conducted by two material experts and two learning material design experts. The second, the student response questionnaire was conducted by 10 students of Vocational high School of Muhammadiyah 1 Metro. Based on the validations process were obtained the result that the average percentage of material experts was 82.01% in the very feasible category. The results of the assessment of students' response questionnaires was obtained the average percentage of 87.55% with a very practical category. Based on the exposure to the results of the validity and practicality test, it can be concluded that the learning materials of sequence and series based on interactive multimedia are valid and practical for learning.